Analysis Of Shooting The Best Ten Athletes Leaders NBA Season 2020-2021 - Siantoro, Gigih (Department of Physical Education, Sport, Health and Recreation, 2021)
Basic skills Shooting is the most well-known and most popular basketball basicand is a part of the trainer's training program. The NBA is a good competition and shooting is an important part of scoring points and winning, it is necessary to analyze the abilities of shooting the best ten athlete leaders NBA season 2020-202. The data obtained will be analyzed using a quantitative descriptive approach. The conclusion of this study is that from the results of data analysis, the results of the data and discussion are the average ability of shooting1 point Ten Athletes Leaders NBA season 2020-2021 is 84.42%, average ability is shooting2 points Ten Athletes Leaders NBA season 2020-2021 by 50.02% and an average ability of shooting3 points Ten Athletes Leaders NBA season 2020-2021 by 39.38%